Systematic review of outbreaks of COVID-19 within households in the European region when the child is the index case - Israel Agaku; Constantine I Vardavas; Esteve Fernández; Nithya Puttige Ramesh; Katerina Nikitara; Jo Leonardi-Bee; Revati Phalkey; Jonathan E Suk; Charlotte Deogan; Katerina Aslanoglou; Orla Condell; Favelle Lamb; et al. (BMJ Publishing Group, 2023)
Objectives This systematic review aims to identify the secondary attack rates (SAR) to adults and other children when children are the index cases within household settings.Methods This literature review assessed European-based studies published in Medline and Embase between January 2020 and January 2022 that assessed the secondary transmission of SARS-CoV-2 within household settings. The inclusion criteria were based on the Population, Exposure, Outcome framework for systematic reviews. Thus, the study population was restricted to humans within the household setting in Europe (population), in contact with paediatric index cases 1-17 years old (exposure) that led to the transmission of SARS-CoV-2 reported as either an SAR or the probability of onward infection (outcome).Results Of 1819 studies originally identified, 19 met the inclusion criteria. Overall, the SAR ranged from 13% to 75% in 15 studies, while there was no evidence of secondary transmission from children to other household members in one study. Evidence indicated that asymptomatic SARS-CoV-2 index cases also have a lower SAR than those with symptoms and that younger children may have a lower SAR than adolescents (>12 years old) within household settings.Conclusions SARS-CoV-2 secondary transmission from paediatric index cases ranged from 0% to 75%, within household settings between January 2020 and January 2022, with differences noted by age and by symptomatic/asymptomatic status of the index case. Given the anticipated endemic circulation of SARS-CoV-2, continued monitoring and assessment of household transmission is necessary.